Prevalence of periodontal tissue disease in children with autistic spectrum disorders - Якубова, Інесса Ігорівна; Ципан, С. Б.; Бардавіль, Д. І.; Василенко, О. І.; Жданова, Т. В.; Бакалінська, С. М.; Стручек, Н. В. (Actual Dentistry, 2020)
Summary. The article describes the characteristics of children with autism spectrum disorders, analysis of literature sources on the quality of oral hygiene and the prevalence of periodontal tissue disorders in children with autism spectrum disorders, presents the results of studying the prevalence of periodontal tissue disorders in children with autism spectrum disorders (main group) (main group) healthy baby (without autism). The aim was to study the prevalence of periodontal tissue diseases in children with autism spectrum disorders. Material and methods. The condition of periodontal tissues was examine in 69 children with autism spectrum disorders (main group) and 23 healthy children (without autism) aged 5 to 6 years. The level of sanitary and hygienic knowledge was determine by an open-ended survey. The quality of oral hygiene was determine by the index of oral hygiene Fedorova-Volodkina. The PMA index was use to evaluate the inflammatory process in the gum area. Statistical processing of the obtained results was carried out using the method of variation statistics, using the software package SPSS Statistica 17/0. Results of the study. In the 5–6 age group with RAS, the average age of the surveyed children was 65.52 months. Boys (84.06 %) dominated the surveyed children; girls were 5.3 times less – 15.94 %. Assessing the hygienic state of PR in points, we found that the average value of the hygiene index in children with autism was 2.70±0.13 and indicates a poor state of hygiene, healthy 1.91±0.08 points and corresponds to a satisfactory state of cavity hygiene mouth. The most common pathology of periodontal tissues – chronic catarrhal gingivitis was reveal. In the examined children with autism spectrum disorders the normal condition of periodontal tissues was diagnosed in 18.84 % of persons, catarrhal gingivitis of mild severity - in 49.28 %; the average – in 31.88 % of children. The iflammation in the gums was indicate by the PMA index, which was 15.31±1.49 %. In healthy children, intact periodontal disease was in 69.57 % of children, mild catarrhal gingivitis reached 30.47 %. Based on the results of our correlation analysis, it was found that the hygiene index of 42.0 % explains the variability of the PMA index, and the improvement of oral hygiene quality reduces the rates of chronic catarrhal gingivitis in children 5–6 years with autism spectrum disorders. Conclusions. The frequency of autism spectrum disorders is increasing every year. A significant number of children, was diagnosed with an increase in the prevalence of gingivitis; data on dental pathology in children with autism spectrum disorders are rather scarce and controversial, prompting further study of this issue in order to improve dental status. Key words: children, autism spectrum disorder, autism, dental caries, gingivitis, self-injurious behavior.